Organizational behavior and change : managing diversity, cross-cultural dynamics, and ethics - Weiss, Joseph W. (Cincinnati, Ohio : South-Western College, 2001)
Organizational behavior in the 21st century. Individual differences and personality. Perception and attribution. Motivation, learning, and rewards. High-performance teams and groups. Communication. Leadership and followership...
Keywords: Management; Workplace; Business ethics; Organization; Diversity in the workplace; Personnel management; Business ethics; Organizational behavior; Organizational change -- Management